THE IMPACT OF ADMINISTRATION, RECORDING, MAINTENANCE, AND TRANSFER OF STATE-OWNED GOODS ON FINANCIAL STATEMENT OPINION WITH THE QUALITY OF FINANCIAL STATEMENTS AS INTERVENING VARIABLES (STUDY ON 35 WORK UNITS WITHIN THE DIRECTORATE GENERAL OF HOUSING, MIN - Hamilah, Hamilah; Amrizal Amrizal; Simon Suban (Dinasti International Journal of Management Science, 2022)
This study purposes to investigate the impact of the administration, recording, maintenance, and transfer of state-owned goods on the opinion of financial statements. The financial statements quality was selected as the intervening variable (study of 35 work units in the Directorate General of Housing, Ministry of PUPR). This study benefits the quantitative approach and sample determination by non-probability sampling method. Specific considerations taken for the purposive sampling technique. The sample in this study was 35 work units with 3 years (2017-2019). Regression model was selected for data analysis by using a computer statistical application program, Eviews 10. The results showed that BMN Registration and BMN Transfers significantly affected the quality of financial reports. BMN Administration, BMN Maintenance do not effect significantly the financial reports quality. BMN Administration, Transfer of BMN, and Quality of BMN financial statements significantly affect financial statement opinion. The recording of BMN and the Transfer of BMN do not effect significantly the opinion of financial statements. The transfer of BMN is proven to significantly affect financial statements' opinions through the financial statements quality as an intervening variable. BMN Administration, BMN Recording, and BMN Maintenance do not effect significantly on financial statement opinion through the quality of financial statements as an intervening variable. And lastly, BMN Administration, BMN Registration, BMN Maintenance.